2017
DOI: 10.1007/s11745-017-4238-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of THP‐1 Macrophages Exposed to Lipoprotein Hydrolysis Products Generated by Lipoprotein Lipase

Abstract: Macrophage lipoprotein lipase (LPL) induces lipid accumulation and promotes atherosclerosis. However, the effects of lipoprotein hydrolysis products generated by LPL on macrophage-derived foam cell formation are not clearly understood. Thus, we analyzed the transcriptomic response to hydrolysis products via microarray analyses on RNA isolated from human THP-1 macrophages incubated with total lipoprotein hydrolysis products generated by LPL. The expression of 183 transcripts was significantly upregulated and 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…In particular, a truncated dyskerin variant that retains intron 12, shows a peculiar cytoplasmic localization and stimulates cell proliferation [19] , raising the possibility that it is involved in additional, previously undetermined, biological functions. Consistent with this view, this specific splice variant has recently been related to lipid metabolism [21] . Here we further explored the impact of this dyskerin isoform on cell physiology, and demonstrated that it exhibits new, uncanonical functions; having the ability to promote a metabolic shift that enhances mitochondrial functionality, producing a globally positive impact on oxidative metabolism and conferring a ROS adaptive response and a growth advantage to cells.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…In particular, a truncated dyskerin variant that retains intron 12, shows a peculiar cytoplasmic localization and stimulates cell proliferation [19] , raising the possibility that it is involved in additional, previously undetermined, biological functions. Consistent with this view, this specific splice variant has recently been related to lipid metabolism [21] . Here we further explored the impact of this dyskerin isoform on cell physiology, and demonstrated that it exhibits new, uncanonical functions; having the ability to promote a metabolic shift that enhances mitochondrial functionality, producing a globally positive impact on oxidative metabolism and conferring a ROS adaptive response and a growth advantage to cells.…”
Section: Introductionsupporting
confidence: 60%
“…In addition, the findings that rotenone and dimethyl malonate treatments have a stronger effect on the survival of 3XF-Iso3 cells demonstrate their higher dependence on OXPHOS compared to controls. Worth noting are the findings by Thyagarajan et al, that Iso3 is upregulated by incubation with hydrolysis products generated by lipoprotein lipase [21] . Since fatty acid β-oxidation occurs in both mitochondria and peroxisomes, the increased level of catalase observed in 3XF-Iso3 cells fits well with the possibility that Iso3 might fuel OXPHOS through this route.…”
Section: Discussionmentioning
confidence: 99%
“…by experimental treatment (Bueno-Silva et al, 2017;Thyagarajan et al, 2017). Additionally, the presence of macrophages can alter the abundance of PCNA in adjacent tissues (Shao et al, 2016) and altered PCNA abundance in porcine intestine has recently been demonstrated, and although staining was certainly more pronounced in the villi crypts, positive PCNA was detected in the tips, though to a much lesser degree (Kang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent literature suggests that simply blocking fatty acid uptake and oxidation to therapeutically induce an M2 to M1 switch in TAMs would greatly oversimplify the metabolic nature of TAM polarization. Which exact combination of saturated and unsaturated fatty acids are critical for M2 polarization and whether or not the full spectrum of hydrolyzed products from circulating lipoproteins instead of just FFAs are required have not yet been fully elucidated [93][94][95][96]. Regardless of the source, CD36 seems to be an active transporter for immunosuppressive TAMs, and studies show these cells have increased lipid accumulation and FAO, which is required for immune suppressive activity in both murine and human macrophages [97,98].…”
Section: Macrophagesmentioning
confidence: 99%